Additive manufacturing of composite materials and functionally graded structures using selective heat melting technique. (15th June 2020) - Markandan, Kalaimani; Lim, Ruijing; Kumar Kanaujia, Pawan; Seetoh, Ian; bin Mohd Rosdi, Muhammad Raziq; Tey, Zhi Huey; Goh, Jun Seng; Lam, Yee Cheong; Lai, Changquan
Abstract: The feasibility of using selective heat melting (SHM) to fabricate composite materials and functionally graded structures was investigated. We report, for the first time, the successful 3D printing of copper (Cu)-polyethylene (PE) composite, iron (Fe)-polyethylene (PE) composite and functionally graded CuO foams using the SHM technique. It was found that a low feed rate, high airflow rate and high airflow temperature were required for efficient delivery of heat from the emitted hot air to the powder bed, so that the PE binder particles can melt and form dense composites with smooth surfaces. The best mechanical properties were exhibited by composites with 80 vol.% PE, as lower PE concentrations led to deficient binding of the metal particles, while higher PE concentrations meant that very few metal particles were available to strengthen the composite. The strength exhibited by Cu-PE composites was comparable to engineering plastics such as polycarbonate, with the added advantage of being electrically conductive. The average conductivity of the samples, 0.152 ± 0.28 S/m, was on par with physically cross-linked graphene assemblies. By subjecting a Cu-PE composite, with Cu concentration graded from 10 vol.% to 30 vol.%, to a high temperature debinding and sintering treatment in air, CuO foam with graded porosity can be obtained. This CuO foam was observed to fail in a layer-by-layer manner under mechanical compression, which is a characteristic of functionally graded materials. Our study shows that, compared to existing 3D printing techniques, SHM can be cheaper, have wider material compatibility, occupy a smaller footprint and potentially induce less residual stresses in the fabricated parts. Therefore, it could be a valuable complement to current additive manufacturing techniques for fabricating mechanically strong composite materials and functionally graded structures.